Aetiologies, comorbidities and causes of death in a population of 133 patients with polyhandicaps cared for at specialist rehabilitation centres. (7th May 2015) - Rousseau, M. C.; Mathieu, S.; Brisse, C.; Motawaj, M.; Grimont, E.; Auquier, P.; Billette de Villemeur, Th.
Abstract: Aim : This study concerns the aetiologies, comorbidities and places and causes of death of a population of persons with severe polyhandicap (PLH). Methods : Based on the medical files of all deceased PLH patients, who were cared for between 2006–2012. Data collected were aetiological diagnosis of the polyhandicap, duration and type of hospitalization, age, place and cause of death, comorbidities: chronic respiratory insufficiency, recurrent attacks of pulmonary infections, urinary infections, active epilepsy, scoliosis, chronic digestive disorders and behavioural problems. Results : One hundred and thirty-three patients died, 70 children and 63 adults. The sex ratio was 84 men to 49 women. The average stay in these institutions was 10 years 4 months. The average age at the time of death was 21 years, in 60% of cases the place of death was in the specialist rehabilitation centres. The causes of death in decreasing order were: pulmonary infections (63.2%), sudden death (18%) and status epilepticus (6.8%); 79.7% of patients suffered from chronic respiratory insufficiency, 60.2% suffered serious scoliosis, 66.9% drug-resistant epilepsy and 78.9% had digestive disorders. The main aetiologies of the polyhandicap were: pre- and perinatal encephalopathies (31.6%), metabolic encephalopathies (18%) and convulsive encephalopathies (11.3%). Conclusion : The main comorbidity and main cause of death in patients with severe PLH is respiratory failure.